Passion-Oranges Syrup Production Gung Pinto Village Tanah Karo - Suprianto, Suprianto; Sumardi, Sumardi; Samran, Samran; Meilani, Debi; Kartika, Dewi (JURNAL PENGMAS KESTRA (JPK), 2023)
Syrup is a beverage product resulting from the production of a mixture of water and sugar at a content of not less than 65%, whether or not ingredients are in the form of food with or without food additives, which have received permission to use according to the regulations of the Food and Drug Supervisory Agency of the Republic of Indonesia. Fruit syrup is made from fresh fruit juice with sugar and the taste and aroma of the fruit. Fruits used in syrup production must have an attractive color, aroma and distinctive taste. Example the taste and aroma of passion fruit (Passiflora edulis S) and sweet orange (Citrus sinensis L). Sweet orange and passion fruit are used as a source of fruit syrup juice. Sweet oranges are widely grown in Indonesia, including North Sumatra, especially in Gung Pinto Village, Tanah Karo. During the main harvest, there is usually a decrease in the price of oranges so that farmers are reluctant to pick the fruit which has been the foundation of their lives. This problem triggers farmers to look for solutions so that their crops do not rot on the trees. Community Service is here to provide a solution by increasing the skills of the community to make Passion Fruit Syrup for the people in the village of Gung Pinto Tanah Karo. The service is carried out by training how to make Passion-Orange syrup by doing direct practice and evaluating the resulting product with a hedonic test. The results showed that the Passion-Orange syrup product showed very good color, taste, aroma and texture, and the public was very happy with the results of the Passion-Orange syrup product. The conclusion of the service shows that the syrup product produced is very good and the community is very happy with the results of the syrup product.